2020
DOI: 10.1039/d0sc01288b
|View full text |Cite
|
Sign up to set email alerts
|

Functional group interaction profiles: a general treatment of solvent effects on non-covalent interactions

Abstract: Functional group interaction profiles are a quantitative tool for predicting the effect of solvent on the free energy changes associated with non-covalent interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(68 citation statements)
references
References 36 publications
0
56
0
9
Order By: Relevance
“… 89 The group of Hunter showed that, contrasting to such bimodal solvent dependencies, local effects due to high effective molarities may be independent of the solvent polarity. 90 , 91 Despite the complexity of many interactions driving supramolecular complexation, interaction strength and solvent dependency can be calculated rather straightforwardly 92 , 93 using literature-derived parameters. 94 As such, solvation influences supramolecular aggregation in numerous ways and many cooperative effects can emerge.…”
Section: The Role Of Solvents In Noncovalent Chemistrymentioning
confidence: 99%
“… 89 The group of Hunter showed that, contrasting to such bimodal solvent dependencies, local effects due to high effective molarities may be independent of the solvent polarity. 90 , 91 Despite the complexity of many interactions driving supramolecular complexation, interaction strength and solvent dependency can be calculated rather straightforwardly 92 , 93 using literature-derived parameters. 94 As such, solvation influences supramolecular aggregation in numerous ways and many cooperative effects can emerge.…”
Section: The Role Of Solvents In Noncovalent Chemistrymentioning
confidence: 99%
“…The SSIP representation of 261 solvent molecules was described previously (see ESI † for full list of solvents). 67 These representations were used to calculate solvation free energies for all solute SSIP values between À10 and +5 in increments of 0.1. Plotting the results gives a unique solvation profile for each solvent, which describes the non-covalent interactions the solvent would make with any solute taking into account the polarity and the concentration of the interaction sites present in the solvent.…”
Section: Resultsmentioning
confidence: 99%
“…As we have previously suggested, the constant of 6 kJ mol À1 in eqn ( 1) is related to the difference between the concentration of the solvent and the standard state of 1 M used to describe the chemical potentials of the solutes. 21,25 Fig. 3 shows experimental data for formation of a 1 : 1 H-bonded complexes in various ether solvents.…”
Section: Solvation Free Energiesmentioning
confidence: 99%